English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

4m squared-3mp+3p-4m

2006-12-03 14:27:04 · 3 answers · asked by Alexis 2 in Science & Mathematics Mathematics

3 answers

4m^2-3mp+3p-4m =
= 4m(m-1)-3p(m-1)
= (m-1)(4m-3p)

check:
(m-1)(4m-3p)=
= m*4m-m*3p-1*4m-1(-3p)
= 4m^2-3mp-4m+3p
= 4m^2-3mp +3p - 4m

2006-12-03 14:32:14 · answer #1 · answered by Mirta G 2 · 0 0

(4mm-3pm)+(3p-4m)
m(4m-3p)+-1(4m-3p)
(-1+m)(4m-3p)

haven't been in math class for a few years, but I think this is right...

2006-12-03 22:36:11 · answer #2 · answered by moobaby09 2 · 0 0

m(4m-3p)+(3p-4m)

2006-12-03 22:39:19 · answer #3 · answered by Brent S 2 · 0 0

fedest.com, questions and answers